Science as a "fixed point"? Quantification and boundary objects in international climate politics. Issue 67 (January 2017) - Lahn, Bård; Sundqvist, Göran
Highlights: Common understandings of climate change see science and policy as clearly separable. This carries a risk of 'flip-flop movements' if scientific purity is challenged. The IPCC 'Bali Box' of emission reduction targets is analysed as a case of this. Climate targets are better understood as simultaneously political and scientific. Abstract: Our understanding of climate change is dominated by quantified scientific knowledge, with science and politics usually seen as operating separately and autonomously from one another. By investigating a particular fact box in the IPCC's Fourth Assessment Report (AR4), this paper challenges the assumption that science and policy can be clearly delineated. The so-called "Bali Box" gained a prominent role in negotiations leading up to the Copenhagen Conference in 2009, as it was widely seen as providing a "fixed point" – a quantified scientific answer to the question of equitable effort-sharing between North and South. This understanding of the Bali Box triggered a backlash, however, when the hybrid character of the box as an assemblage of science, political considerations and moral judgements became evident to actors in the negotiations. The paper employs the notion of boundary objects to analyse the history of the Bali Box, and argues that climate politics will benefit from a richer understanding of the interplay between science and policy. Moving beyond characterizations that place the Bali Box on either side of a clear boundary between the scientific and the political, we suggest focusing instead on what the Box as a hybrid product is doing, i.e. how it simplifies and quantifies, what it covers and what it leaves outside.